Modeling the Construction Sector and Oil Prices toward the Growth of the Nigerian Economy: An Econometric Approach - Peter Uchenna Okoye (Economies, 2018)
This study empirically examined the interrelationship between the construction sector, oil prices, and the actual gross domestic product (GDP) in Nigeria. Using annual economic data from the National Bureau of Statistics (NBS), the OPEC Annual Statistical Bulletin, and econometric statistics, we found that although very strong positive and significant correlations exist between the construction sector output and total GDP output (0.934), the construction sector output and oil prices (0.856), and the total GDP output and oil prices (0.822), these linear relationships only exist for a short time. However, these relationships do not result in any direct causal influence on each other, except for the uni-directional Granger causal relationship that flows from the total GDP output to the construction sector output, which implies that economic activities of other major non-oil sectors stimulate the construction activities in Nigeria. Thus, we argue that neither the construction sector nor the oil prices directly influence the aggregate economy; rather, the other sectors’ activities stimulate the construction sector in Nigeria. Two policy recommendations for achieving the Federal Government’s medium term Economic Recovery and Growth Plan (ERGP) are suggested: (1) the Nigerian government should de-emphasize overreliance on the oil sector through policy readjustment and (2) an urgent need for economic diversification in Nigeria exists, since we revealed that an increase in the aggregate GDP output is due to the activities of other non-oil sectors.